Evaluation of anthropometric indices as predictors of metabolic syndrome: 3-year cohort in Ecuadorian military personnel - German Geovanny Muñoz Gualán; Alberth Patricio Muñoz Gualán (Revista Cubana de Medicina Militar)
Introduction: The metabolic syndrome is a condition that predisposes to the development of cardiovascular and metabolic diseases, where the presence of altered blood pressure, insulin resistance, hyperglycemia, dyslipidemia and abdominal obesity is evaluated in order to know the risk of developing this disease. Objective: To evaluate the anthropometric indices that predict the presence of developing metabolic syndrome in Ecuadorian military personnel. Methods: The research work is quantitative, observational and longitudinal with a correlational scope, it was made analyzing the annual medical records of preventive medicine, in the military personnel of the Army Soldiers Training School "Vencedores del Cenepa", during a 3-year cohort from 2019 to 2021. Results: The study shows an overweight military population, with a prevalence of metabolic syndrome: according to Asociación Latinoamericana de Diabetes criteria of 1 %, 1.66 % and 0.76 %, in the years 2019, 2020 and 2021 respectively; in contrast, according to Adult Treatment Panel III criteria, with a prevalence of 6.67 %, 6.31 % and 5.70 % in the years 2019, 2020 and 2021 respectively. Conclusions: The anthropometric indices, such as the waist-height index, abdominal perimeter and body mass index significantly predict the development of metabolic syndrome in the military personnel of the "Vencedores del Cenepa" Army Soldier Training School.